A series of triple-stranded lanthanide(III) helicates: Syntheses, structures and single molecular magnets. (18th April 2017) - Gao, Xingrui; Li, Hongfeng; Chen, Peng; Sun, Wenbin; Yan, Pengfei
Graphical abstract: A series of triple-stranded β-diketonate-Ln helicates have been assembled, where dimethoxyethane molecules have played a unique role in the crystallization. Abstract: Bis-β-diketones have been proven to be effective for the construction of multiple-stranded helicates, where there commonly are two distinct Ln 3+ centers with subtle geometric difference. In this study, a series of triple-stranded helicates [Ln2 (BTB)3 (DME)2 ]·C6 H14 have been prepared with the ligand H2 BTB and trivalent metallic ions, respectively [Ln = La (1 ), Ce (2 ), Pr (3 ), Eu (4 ), Dy (5 ), Ho (6 ) and Yb (7 ), H2 BTB = 4, 4′-bis(4, 4, 4-trifluoro-1, 3-dioxobutyl)biphenyl and DME = dimethoxyethane]. All products have been fully characterized by IR spectroscopy, elemental analysis, thermogravimetric analysis, and single-crystal X-ray diffraction analyses. Structural analysis reveals that1 –7 are isostructurally crystallized in the orthorhombic space group of Pna 21 and each Ln 3+ ion is ligated to six O atoms of three BTB ligands and two O atoms of one DME molecule. Interestingly, DME molecule as a chelator to the Ln 3+ centers has played a unique role in the crystallization of the triple-stranded helicate1 –7 . Magnetic measurement shows that5 displays significant single-molecule magnetic property, exhibiting magnetic slow relaxation. And the large separation between Dy 3+ ions in the same helicates leads to two distinct magnetic relaxation processes.